1001 inventions the enduring legacy of Muslim civilization - Al-Hassani, Salim T. S. (National Geographic, 2012)
The staggering achievements of these men and women influenced the development of modern mathematics, science, engineering, and medicine. 1001 Inventions: The Enduring Legacy of Muslim Civilization sheds new light on this golden era that was once lost to so many, and celebrates the heritage that we all share.